Internal friction analysis of lath martensite in press hardened steel. Issue 7 (3rd May 2017) - Sulistiyo, D. H.; Cho, L.; Seo, E. J.; De Cooman, B. C.
Abstract : Internal friction (IF) measurements were carried out on a press hardened steel (PHS) after continuous annealing, press hardening and bake hardening. The IF peaks of the PHS with a lath martensite microstructure were analysed by comparison with previously published data. This was supplemented by comparison with the IF spectra of the same steel with a ferrite–pearlite microstructure after deformation at room temperature, and after recrystallisation annealing and quenching. The relation between the IF peaks of PHS, and the γ-peak, Snoek peak and Snoek-Kê-Köster peak observed for ferritic steel is discussed.